Prediction and optimizing residual stress profile induced by cold expansion in aluminum alloys using experimental design (Fracture and Structural Integrity, 2019)
Cold expansion by hardening is a common process used in the aerospace industry to extend the fatigue lifetime of assembly holes, through a field of high compressive tangential residual stresses. The understanding and the control of the residual stresses are thus important, since it can be beneficial to improve lifetime of the structures. The main objective of this work is to establish and validate a predictive model of residual stresses generated by cold hardening. This technique can be an effective ways for industrials allowing an estimation of the fatigue lifetime of parts according to the process parameters or to determine the optimal parameters to maximize fatigue lifetime. An experimental setup was used to highlight the effect of expansion degree, thickness of the part and yield strength on the residual stresses profiles. Moreover, the proposed mathematical models were used to determine the optimal values of the various factors for the residual stress profiles prediction at any factor values, in order to achieve maximum service life after repair of a cracked structure or to delay crack initiation and growth in riveted or bolted structures. Besides, the modelling permits us to highlight the effect of interaction of these factors on the residual stresses profiles.
Keywords: Cold expansion; Residual stress; Prediction; Experimental design; Interaction; Fatigue life